2021
DOI: 10.3390/membranes11080589
|View full text |Cite
|
Sign up to set email alerts
|

A New Activated Sludge Model with Membrane Separation–Implications for Sewage and Textile Effluent

Abstract: A new model for the activated sludge process with membrane separation is presented, based on the effective filtration size. A new size threshold is imposed by the membrane module. The model structure requires a modified fractionation of the chemical oxygen demand and includes chemical oxygen demand fractions entrapped in the reactor or in the flocs as model components. This way, it offers an accurate mechanistic interpretation of microbial mechanisms taking place in membrane activated sludge systems. Denim pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Modelling results suggested an f BX value of 1.5 for V D / V T fractions between 0.1–0.3 and 1.35 for a V D / V T ratio of 0.4. A similar work 70 on process modelling also indicated that the operating conditions of the anoxic zone with a sludge age, θ XD , higher than 4.0–5.0 would result in complete consumption of rapidly hydrolysable COD fraction, S H , i.e., complete utilization of soluble biodegradable COD, so that a modified version of the equation would apply and still yield a conservative value for N DP : NDPgoodbreak=1YNHE2.86[]SnormalS0goodbreak+SnormalH0goodbreak+fBX()VDVTXnormalS0 Equation (19) provides the best empirical approximation for the assessment of N DP, in light of all supporting scientific information. Its numerical evaluation for the design procedure may be carried out using the relevant experimental data used to derive the COD fractionation of Ambarlı sewage, namely S S0 = 36 mg L −1 ; S H0 = 125 mg L −1 ; X S0 = 292 mg L −1 ; Y NHE = 0.24 mg cell COD/mg COD, together with an f BX value of 1.35 suggested by process modelling 68 .…”
Section: Experimental Evaluationmentioning
confidence: 76%
See 1 more Smart Citation
“…Modelling results suggested an f BX value of 1.5 for V D / V T fractions between 0.1–0.3 and 1.35 for a V D / V T ratio of 0.4. A similar work 70 on process modelling also indicated that the operating conditions of the anoxic zone with a sludge age, θ XD , higher than 4.0–5.0 would result in complete consumption of rapidly hydrolysable COD fraction, S H , i.e., complete utilization of soluble biodegradable COD, so that a modified version of the equation would apply and still yield a conservative value for N DP : NDPgoodbreak=1YNHE2.86[]SnormalS0goodbreak+SnormalH0goodbreak+fBX()VDVTXnormalS0 Equation (19) provides the best empirical approximation for the assessment of N DP, in light of all supporting scientific information. Its numerical evaluation for the design procedure may be carried out using the relevant experimental data used to derive the COD fractionation of Ambarlı sewage, namely S S0 = 36 mg L −1 ; S H0 = 125 mg L −1 ; X S0 = 292 mg L −1 ; Y NHE = 0.24 mg cell COD/mg COD, together with an f BX value of 1.35 suggested by process modelling 68 .…”
Section: Experimental Evaluationmentioning
confidence: 76%
“…Modelling results suggested an f BX value of 1.5 for V D /V T fractions between 0.1-0.3 and 1.35 for a V D /V T ratio of 0.4. A similar work 70 on process modelling also indicated that the operating conditions of the anoxic zone with a sludge age, ⊔ XD , higher than 4.0-5.0 would result in complete consumption of rapidly hydrolysable COD fraction, S H , i.e., complete utilization of soluble biodegradable COD, so that a modified version of the equation would apply and still yield a conservative value for N DP :…”
Section: Denitrification Potentialmentioning
confidence: 97%
“…However, the hydrolysis half-saturation constants were found to be lower than the values in the literature. 37,38…”
Section: Wileyonlinelibrarycom/jctbmentioning
confidence: 99%
“…23,47 Later, relevant microbial mechanisms of super-fast MAS systems for organic carbon removal could be assessed by means of model analysis for domestic sewage and selected industrial wastewaters. 48,49 A review, after evaluating all existing information, argued that in the near future, the activated sludge process will be reshaped and 'the novel AS configuration shall not include gravity settling and it will be operated at extremely low ⊔ X levels of <2.0 d'. 50 The evaluation focused on the energy conservation aspect mainly because it constituted the rate-limiting step of the energy recovery mechanism.…”
Section: Effective Energy Conservationmentioning
confidence: 99%